The forms of physical activity chosen by young adults - Popiołek, Joanna; Kusz, Monika; Alzubedi, Adam; Konopelko, Michał (Journal of Education, Health and Sport, 2018)
The positive impact of regular physical activity is a widely recognized fact. The WHO recommends that people of all ages exercise 30 minutes of exercise every day. In the context of the sedentary lifestyle and changes in social behavior patterns in recent years, there is a need to examine the habits of young adults regarding physical activity. The aim of the study was to investigate which forms of exercises are preferred by young adults and how much time they devote to them.The study was conducted on a group of 42 people (16 men and 26 women). Respond-ents were asked about the forms of physical activity they choose most often and the time during the week they devote to them. A written questionnaire with multiple-choice questions was used to obtain the data. The most common form of activity chosen by young adults was walking (66.7% of the group). The next forms were dancing (42.9%) and swimming (38.1%). Referring to time issues, respondents spent 209 minutes a week on physical activity (SD 190). Men spent 315 minutes and women 143 minutes per week. At the same time, respondents spent the most time on walking (55 minutes per week on average), 31 minutes and 29 minutes per week for gym training and dancing respectively. Among young adults, the most-chosen form of physical activity was walking, which may be related to its undemanding character. Young adults devoted enough time to physical activity according to WHO recommendations. They care about their physical condition by participating both moderate and intense physical activities.